The Japanese Communist Party permanent opposition, but moral compass - Berton, Peter; Atherton, Sam (Routledge Contemporary Japan series ;, 2018)
This book provides an historical overview of the Japanese Communist Party from its foundation to the present. It outlines the development of the party, explores its stance on key issues and discusses how the party has set a high moral tone, avoiding compromising coalitions with other parties, being intolerant of corruption within its own ranks, and frequently and consistently opposing the ruling Liberal Democratic Party. The book emphasizes the importance for Japan of this moral approach as the conscience of the nation, especially as the present Abe government moves Japan to the right, even though the Japanese Communist Party has never gained power and is never likely to.